Investigating the Mesh Size Selectivity of Olive Flounder (Paralichthys olivaceus) Gillnets for Fisheries Resource Management in the East Sea - Hyun-Ji Yu; Young Il Seo; Jae-Hyeong Yang; Jeong-Ik Baek; Seong hun Kim (Fishes, 2023)
This study aimed to evaluate the mesh selectivity of gillnets used in olive flounder (Paralichthys olivaceus) fishing by examining the distribution of total length (TL) across various mesh sizes. A marine fishing experiment was conducted at Gajin Harbor in Goseong County, Gangwon Province, employing experimental gear with four different mesh sizes: 90, 105, 135, and 150 mm. Mesh selectivity analysis involved a comparative assessment of selectivity curve methods through normal, log-normal, and bi-normal functions. Among these, the bi-normal function demonstrated the best fit for estimating the mesh selectivity curve within the SELECT model. The critical finding was the net size at which 50% of the minimum landing size (35 cm in TL) of olive flounder was selected, ranging from 108.7 to 121.1 mm. According to the bi-normal function curve, this size was estimated as 114.0 mm. Our findings indicate that using a mesh size larger than the theoretically estimated size in mesh selectivity analysis can further decrease the catch of immature individuals. These findings provide essential data for devising strategies to efficiently utilize and manage olive flounder resources.